The Competitiveness of COFCO Through Transnational Development - Tengzhong Xu; Elena V. Kolganova (Communications of International Proceedings, 2021)
At the beginning of the XXI century, most of the large national companies in developed countries became transnational. In recent years, the trend of turning international firms into global companies has been formed, global production and sales networks are actively developing, global markets are being formed, and the role of international institutions is increasing. The development of globalization has led to a change in the nature and toughening of competition. The new content of the competitiveness of the world's largest companies is associated with the global nature of operations, the widespread use of information technologies, the turbulent external environment, the tightening of competition between transnational corporations of developed countries and developing economies, the development of inter-firm cooperation, and changes in the nature and methods of state regulation of the economy. Currently, there is a steady increase in the competitiveness of a small group of leading transnational corporation-leaders of their industries and sectors of the economy, which has become an important feature of the modern world economy.
Keywords: Transnational Corporation; Globalization; Competitiveness; Development